Review on chemical constituents, pharmacological activities, and clinical applications of Pleione orchid - Xiaotong Ji; Shunshun Wang; Shasha Wu; Siren Lan; Donghui Peng; Danqi Zeng; Zhong-Jian Liu (Medicinal Plant Biology)
Traditional Chinese medicine, a cornerstone of Chinese civilization, boasts a rich history spanning thousands of years. The Pleione orchid, renowned for its medicinal properties, is a primary source of Pseudobulbus Cremastrae seu Pleiones (PCsP, 山慈菇). Given its therapeutic effects, there has been a surge in research related to Pleione in recent years, underscoring the need for a comprehensive review of this medicinal plant. Here, the latest studies on the chemical constituents, pharmacological effects, and clinical applications of Pleione are summarized, and the shortcomings of current research presented. This review encompasses advancements made over the past few decades, providing a theoretical foundation for both new drug development and the clinical application of Pleione. It also aids in the effective utilization and industrialization of medicinal and edible orchids, thereby promoting their sustainable development and societal benefits.